Development of Intelligent Driver Assistant System for Cognitive Cars - Jishma, C. P.; Praharshitha, B. V.; Laxmi, Arpita; Anusha, S. K.; Kumar, J. Satheesh (Journal of ISMAC, 2022)
Automation in vehicles is essential in present day’s road conditions. Many of the accidents are happening due to wrong behaviour, drowsiness and human inattention. The vehicle drivers are expected to be more attentive during their driving period. As a normal human being, it is usual that sometimes there may be a lapse in attention due to many environmental factors. Therefore, automation in cars is really required to overcome many uncertainties faced in real-time scenarios. This paper explores various automation techniques used in vehicles. Cognitive cars proposed in the paper, functions based on machine learning Algorithms. These cars travel from source to destination without any human intervention. The main objectives included in the paper are lane detection, obstacle detection, road signs detection and traffic lights detection. In near future cognitive cars will be preferred for the modern communities due to its intelligent features and increased safety aspects. It will be an asset of the future generation.